Developments and Emerging Trends in the Global Treatment of Chronic Rhinosinusitis From 2001 to 2020: A Systematic Bibliometric Analysis - Zhou, Fangwei; Zhang, Tian; Jin, Ying; Ma, Yifei; Xian, Zhipeng; Zeng, Mengting; Yu, Guodong (Frontiers in Surgery, 2022)
Background Research on the treatment of chronic rhinosinusitis (CRS) has increased in recent decades. We undertook a bibliometric and visualization analysis of studies on CRS treatment to track research trends and highlight current research “hotspots”. Methods Original publications related to CRS treatment were obtained from the Science Citation Index-Expanded (SCI-E) and Social Sciences Citation Index (SSCI) databases in the Web of Science Core Collection (WoSCC) of Clarivate Analytics between 2001 and 2020. The country/region, institution, author, journal, references, and keywords involved in this topic were extracted using CiteSpace and VOSviewer to identify and analyze the research focus and trends in this field. Results In the previous two decades (especially after 2015), the number of publications on CRS treatment has grown markedly. With regard to publications and access to collaborative networks, the leading country was the USA. High-frequency keywords were “CRS,” “endoscopic sinus surgery,” “sinusitis,” “nasal polyps,” “asthma,” “rhinosinusitis,” “management,” “diagnosis,” “outcomes,” and “quality of life.” Inspection of keyword bursts suggested that “clinical practice guideline,” “adult CRS,” “innate lymphoid cell,” “recurrence,” and “mepolizumab” are the emerging research hotspots. The timeline view of the cluster map revealed that biologic agents have become an up-and-coming “hot topic” in CRS treatment in recent years. Conclusion Academic understanding of CRS treatment has improved markedly over the past 20 years. We study analyzed the papers objectively, methodically, and comprehensively, and identified hotspots and prospective trends in the field of CRS treatment. These results will aid rhinologists in gaining greater insight into CRS treatment strategies and identifying the changing dynamics of CRS research.